A conceptual trajectory multidimensional model: an application to public transportation (2011)
Currently, thanks to global positioning systems technologies and mobile devices equipped with sensors, a lot of data about moving objects can be collected, e.g., data related with the trajectories which are followed by these devices. On the other hand, Data Warehouses (DWs), usually modeled by using a multidimensional view of data, are specialized databases used to support decision-making processes. Unfortunately, conventional DWs offer little support for managing trajectories. Although there are some proposals that deal with trajectory DWs, none of them are devoted to conceptual multidimensional modeling. In this paper, we extend a conceptual spatial multidimensional model by incorporating a trajectory as a fi rst-class concept. In order to show the expediency of our proposal, we illustrate it with an example related to public transportation.